Interest in Learning Religiousness Among Housewives in Ta'lim Assembly Activities in Suka Negara Village - Pemi Aulia; Atrik Salzalela; Rossi Delta Fitrianah; Aziza Aryati (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The purpose of this study was to determine the interest in learning the religion of housewives in the ta'lim assembly activities in Suka Negara village, Marga Sakti Sebelat district, North Bengku Regency. Using descriptive qualitative methods with data collection techniques through observation, interviews, documentation. The results of this study revealed that the interest in learning about the religion of housewives in the ta'lim assembly activities in Suka Negara village, Marga Sakti Sebelat sub-district, North Bengkulu Regency was good, when viewed from every meeting there were always congregations present, although not all members were present. The activity of the Miftahul Jannah ta'lim assembly, Suka Negara village, Marga Sakti Sebelat District, North Bengkulu Regency is an activity that takes turns from the homes of members of the congregation, this activity is carried out every Friday. The existence of this ta'lim assembly is very important for the Suka Negara village community because there are many positive things that have been obtained, the activities of this ta'lim assembly have been carried out well. So it can be said that interest in learning is a choice of pleasure in carrying out activities and can arouse enthusiasm to fulfill the desire to learn, as well as the interests of these mothers